Electrochemical oxidation intermolecular [3 + 2] cycloaddition of N-tosylhydrazones and quinolone derivatives to access fused 1, 2, 4-triazole compounds. (12th January 2023) - Zhang, Wei; Jiang, Rui; Mu, Yangxiu; Hong, Yu; Wan, Yaya; Yang, Zhixiang; Tang, Dong
Graphical abstract: Abstract: A simple and convenient method for the electrosynthesis of fused 1, 2, 4-triazoles with two components of N -tosylhydrazones and quinolone derivatives has been established. The electrochemical method could be smoothly carried out at room temperature with the addition of KI and base to afford the desired products in good yields, which has potential for the large preparation of 1, 2, 4-triazole derivatives due to the feature of operationally simple and without usage of excess chemical oxidants.